Pharmacological effects and application prospects of mussel adhesive proteins - An, Junsha; Hou, Zengmiao; Li, Jiaqi; Bi, Qian; Huang, Shile; Peng, Cheng; Peng, Fu (Frontiers in Pharmacology, 2025)
Mussel adhesive proteins (MAPs) are natural proteins derived from Mytilus edulis, renowned for their exceptional adhesive properties. These proteins, rich in 3,4-dihydroxyphenylalanine (DOPA) residues, enable mussels to adhere firmly to surfaces in challenging environments. Due to these unique biochemical and mechanical characteristics, MAPs have attracted significant attention in the biomedical field, offering promising applications in wound healing, drug delivery, tissue engineering, and cosmetics. Recombinant MAPs (rMAPs), in particular, hold great potential due to their enhanced properties, including antioxidant, anti-inflammatory, antibacterial, and cell-protective effects. They are increasingly being explored for their role in tissue repair, skin regeneration, and targeted drug delivery systems. Despite challenges in recombinant production, toxicity control, and underwater adhesion efficiency, ongoing advancements in genetic engineering and protein design are expanding the application prospects of rMAPs. This review explores the structure, pharmacological effects, and biomedical applications of MAPs, with a focus on the potential of rMAPs in precision medicine, drug delivery, and tissue regeneration, while highlighting the challenges and future directions for their development.